The Contributing Factors of Pragmatic Failure in Uzbek’s ELT Classrooms (Eurasian Journal of Learning and Academic Teaching, 2023)
Pragmatic failure is the inability to understand what is meant by what is said, which can often lead to misunderstanding or confusion in cross-cultural communication. For this reason, the present article explores the contributing factors of pragmatic failure in Uzbek’s ELT Classrooms. The following factors as teacher-centered teaching; lack of authentic input; teaching English without considering the cultural differences; linguistic competence oriented evaluation system were found out.